Aktivitas Fisik dan Permainan Konstruktif dalam Pengembangan Regulasi Diri dan Pemecahan Masalah Anak Usia Dini - Kamil, Nurhusni; Wahyuni, Sri; Zahrah, Faiqatuz; ‘Azzam, Dimas Ahnan (Faculty of Education and Teacher Training of UINSI Samarinda, 2026)
This study examines the role of structured physical activity and constructive play in supporting young children’s self-regulation and problem-solving. A qualitative case study design was conducted with children aged 4–6 years. Data were collected through activity observations, interviews with teachers and parents, and documentation of play processes. Data were analyzed using data reduction, data display, and conclusion drawing, while credibility was ensured through source triangulation. The findings indicate that structured physical activity, particularly gross-motor games, helps children control impulses, sustain attention, and regulate emotions across play and learning situations. Constructive play with blocks and puzzles encourages children to plan actions, test strategies, think logically, and resolve challenges independently. These findings highlight the importance of designing early childhood learning that intentionally integrates structured physical activity and constructive play to foster self-regulation and problem-solving development.